2021
DOI: 10.3390/rs13081453
|View full text |Cite
|
Sign up to set email alerts
|

Remote Sensing of Forest Structural Changes Due to the Recent Boom of Unconventional Shale Gas Extraction Activities in Appalachian Ohio

Abstract: Dense unconventional shale gas extraction activities have occurred in Appalachian Ohio since 2010 and they have caused various landcover changes and forest fragmentation issues. This research investigated the most recent boom of unconventional shale gas extraction activities and their impacts on the landcover changes and forest structural changes in the Muskingum River Watershed in Appalachian Ohio. Triple-temporal high-resolution natural-color aerial images from 2006 to 2017 and a group of ancillary geographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…The development of COG and UOG has documented impacts on land resources in the Appalachian Basin. These include increasing forest fragmentation (Drohan et al 2012 , Donnelly et al 2017 , Langlois et al 2017 , Liu 2021 ), accelerated forest canopy loss (Young et al 2018 ), disturbance to avian communities (Farwell et al 2020 ; Johnson et al 2010 ), and impairment of water quality caused by increased sedimentation in local stream systems (Olmstead et al 2013 ). In the current study, environmental monitoring was focused on land area disturbance and terrain features associated with well pads.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The development of COG and UOG has documented impacts on land resources in the Appalachian Basin. These include increasing forest fragmentation (Drohan et al 2012 , Donnelly et al 2017 , Langlois et al 2017 , Liu 2021 ), accelerated forest canopy loss (Young et al 2018 ), disturbance to avian communities (Farwell et al 2020 ; Johnson et al 2010 ), and impairment of water quality caused by increased sedimentation in local stream systems (Olmstead et al 2013 ). In the current study, environmental monitoring was focused on land area disturbance and terrain features associated with well pads.…”
Section: Discussionmentioning
confidence: 99%
“…A more important observation is the fact that UOG wells were drilled in grassland areas significantly more often than COG wells. While research in the Appalachian basin has shown that UOG can have significant impacts on core forest (Drohan et al 2012 , Donnelly et al 2017 , Langlois et al 2017 , Liu 2021 ), it is important to note that from a forest fragmentation standpoint, COG wells would have greater cumulative impacts based on development patterns and density (Appiah et al 2020 ; Scanlon et al 2017 ) than UOG wells in WV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The local land cover and ecological environment are often artificially changed during the process of shale oil/gas development [14]. Therefore, acquiring land cover through a long-term remote sensing time series to monitor land disturbance provides the most important and practical method for monitoring shale oil/gas development [15].…”
Section: Introductionmentioning
confidence: 99%
“…Extensive infrastructure is required to facilitate shale gas extraction including well pads, water impoundments, pipelines, and access roads. Pipelines comprise the single largest portion of the industry's spatial footprint (Farwell et al 2016, Donnelly et al 2017, Langlois et al 2017, Young et al 2018, Liu 2021) and are the primary cause of habitat loss and fragmentation in a forested landscape (Langlois et al 2017, Liu 2021). One mitigation policy recommended to reduce the loss of core forest is to collocate shale gas pipelines with existing surface disturbance whenever feasible, including road networks and right‐of‐way corridors (Bearer et al 2012, Pennsylvania Department of Conservation and Natural Resources [PADCNR] 2014, Abrahams et al 2015, Donnelly et al 2017).…”
mentioning
confidence: 99%